COEVOLUTION AND RELATIONSHIP OF AHEES ON FODDER PLANTS (HOMOPTERA, APHIDINEA) - АlijonKarimovich Khusanov; TojimatovichSobirov, Ozodbek (International Journal of Psychosocial Rehabilitation, 2024)
The article examines the features of forage specialization and the co-evolution of aphids in the “parasite-host” system. Aphids of the genera Eriosoma Leach. (3 species), Tetraneura Hart. (2 species) and aphids Kaltenbachiella pallida (Halid.) Briefly use the leaves of the elm (Ulmusdensa), for the development of founders and winged migrants. Elm-gall aphids, as representatives of one guild, simultaneously use the fodder plant by subdividing ecological niches.The random distribution of aphids on the fodder plant follows Poisson’s law (